2016
DOI: 10.1039/c6ra01437b
|View full text |Cite
|
Sign up to set email alerts
|

Dealuminated BEA zeolite for selective synthesis of five-membered cyclic acetal from glycerol under ambient conditions

Abstract: BEA zeolite is modified using phenoldisulfonic acid to change catalyst characteristics, which helps to form a single cyclic product. A new term called volume space acidity (VSA) provides volume space available for dioxane to dioxalane rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…a novel method to nely tune the acidity of H-beta zeolites. It has been found that dealumination of beta zeolites by steaming, 17 leaching with mineral acids such as HCl, 18 and treatments with chemicals such as ammonium hexauorosilicate, 19 and organic acids 20,21 are effective for this purpose. Among these approaches, acid leaching is considered to be the most feasible route from the point of view of environmental protection and industrial application, but the negative effects of dealumination by acid leaching are structural changes in zeolite crystals and uncontrollable loss of framework aluminum atoms that decreases active sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a novel method to nely tune the acidity of H-beta zeolites. It has been found that dealumination of beta zeolites by steaming, 17 leaching with mineral acids such as HCl, 18 and treatments with chemicals such as ammonium hexauorosilicate, 19 and organic acids 20,21 are effective for this purpose. Among these approaches, acid leaching is considered to be the most feasible route from the point of view of environmental protection and industrial application, but the negative effects of dealumination by acid leaching are structural changes in zeolite crystals and uncontrollable loss of framework aluminum atoms that decreases active sites.…”
mentioning
confidence: 99%
“…By combining these results and the 27 Al (MQ) MAS NMR results, it can be seen that, partial framework aluminum atoms were removed from the H-beta zeolite during the organic acid treatments. Because extra-framework Al species in zeolites are responsible for weak acid sites, 21 the decreased quantities of weak L and B acids of the beta zeolites aer organic acid leaching (Table 4) indicate the extraction of most extraframework Al species from the zeolite pore channels. The oxalic acid leaching not only removes framework aluminum atoms from the zeolite framework in large amount but also brings them out of the zeolite pore channels leading to opener pore channels, i.e., the oxalic acid leaching has dual roles: the rst is to hydrolyze Al-O-Si linkages (see step 1), and the second is as a chelating agent to complex the tetrahedral Al species and then to move the resulting species out of the pore channels (see step 2(a)).…”
mentioning
confidence: 99%
“…Various reported catalysts were compared for the solketal conversion (Table ). 1PDSABEA sample showed 100% selectivity, but modification of the BEA catalysts to be trickier, due to controlled dealumination. Different metal loaded catalysts showed decrease in their activity after 3–4 recycles with relatively poor selectivity due to leaching.…”
Section: Resultsmentioning
confidence: 99%
“…Different metal loaded catalysts showed decrease in their activity after 3–4 recycles with relatively poor selectivity due to leaching. BEA sample, also showed deactivation for the acetone due to high reactivity after several usage cycles. The HC‐catalytic material used for the present work is less expensive as well as eco‐friendly in nature, loading or functionalization is very easier than the any other catalytic systems.…”
Section: Resultsmentioning
confidence: 99%
“…conversion and selectivity of cyclic imide and other two has lower acidity than alumina but comparable to pillared clays, hence the yield and conversion are similar to pillared clays. With these Zeolites were are used for the reaction, among the zeolites used, HBEA and HÀY showed similar conversions and cyclic imide selectivity, because, both are having higher pore volume and pore size, even though ZSM-5 having higher acidity, it gives lower conversion may due to its constrained channels having uniform pore size 27,37 . While other two has cage like structure with higher pore size but those have lower acidity than ZSM-5 but more compared metal oxides and clays hence giving more yield than all the samples used.…”
Section: Samples Conversion Of Bdc Yield Of Amic Acid Yield Of Cyclicmentioning
confidence: 99%